Sub‐second heat inactivation of coronavirus using a betacoronavirus model. Issue 5 (3rd March 2021) - Jiang, Yuqian; Zhang, Han; Wippold, Jose A.; Gupta, Jyotsana; Dai, Jing; de Figueiredo, Paul; Leibowitz, Julian L.; Han, Arum
Abstract: Heat treatment denatures viral proteins that comprise the virion, making the virus incapable of infecting a host. Coronavirus (CoV) virions contain single‐stranded RNA genomes with a lipid envelope and four proteins, three of which are associated with the lipid envelope and thus are thought to be easily denatured by heat or surfactant‐type chemicals. Prior studies have shown that a temperature as low as 75°C with a treatment duration of 15 min can effectively inactivate CoV. The degree of CoV heat inactivation greatly depends on the length of heat treatment time and the temperature applied. With the goal of finding whether sub‐second heat exposure of CoV can sufficiently inactivate CoV, we designed and developed a simple fluidic system that can measure sub‐second heat inactivation of CoV. The system is composed of a stainless‐steel capillary immersed in a temperature‐controlled oil bath followed by an ice bath, through which virus solution can flow at various speeds. Flowing virus solution at different speeds, along with temperature control and monitoring system, allows the virus to be exposed to the desired temperature and treatment durations with high accuracy. Using mouse hepatitis virus, a betacoronavirus, as a model CoV system, we identified that 71.8°C for 0.51 s exposure is sufficient to obtain >5 Log10 reduction in viral titer (starting titer: 5 × 10 7 PFU/ml), and that when exposed to 83.4°C for 1.03 s, the virus was completely inactivated (>6 Log10 reduction). Abstract : A simple system was developed to investigate sub‐second heat inactivation of coronaviruses. Using mouse hepatitis virus, a betacoronavirus, as a model system, the authors identified that 71.8°C for 0.51 s exposure is sufficient to obtain >5 Log10 reduction in viral titer, and that when exposed to 83.4°C for 1.03 s, the virus was completely inactivated. Validated by a COMSOL simulation on temperature distribution, these findings are essential for developing sub‐second heat disinfection applications.